Innate host selection in Anopheles vestitipennis from southern Mexico. - Ulloa García, Armando; Arredondo Jiménez, Juan Ignacio; Fernández Salas, Ildefonso; Rodríguez, Mario Henry; González Cerón, Lilia (American Mosquito Control Association, 2004)
We assessed the degree of host specificity of the purported anthropophilic and zoophilic populations of Anopheles vestitipennis. A series of experiments were conducted in an experimental hut with 3 compartments lined with nylon netting. A central release compartment and 2 side compartments were each baited with equivalent surface area of human and animal baits. Wild An. vestitipennis collected on each host, as well as corresponding F1 mosquitoes, were released in the central compartment. Overall, 22% (166/748) of all mosquitoes collected on humans were recaptured in the human compartment, whereas 23% of mosquitoes originally collected on animals were recaptured in this compartment. Experiments with F1 females resulted in 59% human selection rates, a 2.6 times increase compared with wild anthropophilic females, while a 1.2 times decrease in human selection rates (from 24% to 20%) was observed in F1 of wild zoophilic females. Host selection experiments in the Lacandón Forest revealed the same trend. These findings suggested that the complex mode of inheritance that resulted in female mosquitoes showing a stronger tendency to return to their preferred host was obscured by the nature of the method of collection, i.e., wild parental females selecting a host either innately or opportunistically, the majority of which were likely innately attracted. This was revealed by F1 females, of which, when given the choice to select a host, a higher proportion opted for the preferred one. The results presented here are in accordance with other studies that identified a subpopulation of An. vestitipennis in southern Mexico with higher anthropophily.